1987
DOI: 10.1016/0022-510x(87)90155-9
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies against human astrocytomas and their reactivity pattern

Abstract: SUMMARYThe establishment of hybridomas after fusion of X63-Ag8.653 mouse myeloma cells and splenocytes from BALB/c mice hyperimmunized against human astrocytomas is presented. The animals were primed with 5 x 106 chemically modified uncultured or cultured glioma cells. Six weeks after the last immunization step an intrasplenal booster injection was administrated and 3 days later the spleen cells were prepared for fusion experiments. According to the specificity analysis of the generated antibodies 7 hybridoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…GAA-positive/GFAP-positive cells can be of either neoplastic or reactive origin, because GAA positive material could have been delivered from necrotic tumor cells and then have been incorporated by reactive cells. The recognition of reactive astrocytes by glioma-directed MAbs has been described (Stavrou et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GAA-positive/GFAP-positive cells can be of either neoplastic or reactive origin, because GAA positive material could have been delivered from necrotic tumor cells and then have been incorporated by reactive cells. The recognition of reactive astrocytes by glioma-directed MAbs has been described (Stavrou et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Using human astrocytoma cells as immunogen, we have established hybridoma clones producing antibodies, which react predominantly with GAA (Stavrou et al, 1987). In the present study, GFAP and 2 MAb-defined GAA are demonstrated simultaneously in human astrocytomas in order to identify cells which were recognized by anti-glioma MAbs .…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…23 Infection with HIV-I was achieved by cocultivation of 85HG-66 cells with T-lymphoma cells (KE37/I) productively infected with HIV-illB. Expression ofHIV-1 antigen following exposure of cells to virus was monitored at a single-cell level by direct immunoperoxidase staining (IPS).…”
Section: Establishment Of Chronically Hiv-i-infected Human Glioma Celmentioning
confidence: 99%
“…Accordingly, SGCs have high potential to express symbiotic markers. Many types of whole cells have been used as antigens to immunize mice and generate antibodies that could recognize cell-surface antigens, such as human astrocytomas 19 , human B lymphoblastic leukemia cells 20 , Burkitt’s lymphoma tumor cells 21 , sheep red blood cells 22 , and killed whole cells of Streptococcus mutans 23 . Therefore, in the present study, whole SGCs were used as the antigen to generate symbiosis-specific antibodies for possible symbiotic markers to investigate the characteristics of cnidarian-dinoflagellate endosymbiosis.…”
Section: Introductionmentioning
confidence: 99%